Prolactin has a pathogenic role in systemic lupus erythematosus - Jara-Quezada, Luis (Henry Stewart Talks, 2019)
Introduction to the role of prolactin in systemic lupus erythematosus, Prolactin and innate immune response, Prolactin and adaptive immune response, Role of prolactin in autoimmune diseases, Prolactin, immunogenetics, and systemic lupus erythematosus, Prolactin, immune response, and human systemic lupus erythematosus, Prolactin, pregnancy, and systemic lupus erythematosus, Prolactin target therapy for SLE